GSDMD-NETs in patients with sepsis-induced coagulopathy and their interaction with glycocalyx damage - Shan, Xiaoxi; Yu, Songmei; Tang, Zhaoying; Yang, Ping; Dong, Lixia (Frontiers in Immunology, 2025)
IntroductionNeutrophil extracellular traps (NETs) play a critical role in inflammation and coagulation imbalance. Recent studies have demonstrated that activation of gasdermin D (GSDMD) protein and its pore-forming activity are essential drivers of NET generation. This study investigated the association between GSDMD-NETs axis activation and sepsis-induced coagulopathy (SIC), as well as the potential association with glycocalyx damage.Materials and MethodsA prospective cohort of 70 sepsis patients (35 with SIC, 35 non-SIC) admitted to a respiratory intensive care unit was analyzed. This study was registered at the Chinese Clinical Trial Registry (ChiCTR) with the registration number ChiCTR2500100284. The trial can be accessed at https://www.chictr.org.cn/bin/project/edit?pid=266738. Plasma levels of GSDMD-NETs biomarkers (N-GSDMD, MPO-DNA) and glycocalyx injury markers (syndecan-1, MMP-9) were measured via ELISA. Clinical outcomes, thrombotic/hemorrhagic events, and biomarker correlations were evaluated using logistic regression, ROC analysis, and Pearson’s correlation.ResultsCompared to non-SIC patients, the SIC group exhibited higher rates of viral infections (31.4% vs. 11.4%, P = 0.043), hemorrhagic events (48.6% vs. 17.1%, P = 0.005), and in-hospital mortality (40.0% vs. 17.1%, P = 0.034). SIC patients demonstrated significantly elevated GSDMD-NETs axis biomarkers (N-GSDMD: 481.302 vs. 539.033, P < 0.001; MPO-DNA: 376.708 vs. 461.847, P < 0.001) and glycocalyx damage markers (syndecan-1: 367.754 vs. 431.186, P=< 0.001; MMP-9: 121.550 vs. 133.931, p = 0.009). GSDMD-NETs biomarkers independently predicted SIC risk (MPO-DNA: OR 1.015, 95% CI 1.005–1.025; N-GSDMD: OR 1.018, 95% CI 1.005–1.031). ROC analysis revealed predictive efficacy for SIC (N-GSDMD: AUC 0.786; MPO-DNA: AUC 0.772), with enhanced performance for their combination (AUC: 0.859). Similarly, the combined biomarkers predicted mechanical ventilation (AUC: 0.755) and mortality (AUC: 0.767). MPO-DNA correlated with syndecan-1 (r = 0.856, p < 0.001) and MMP-9 (r = 0.595, p < 0.001), while N-GSDMD correlated with syndecan-1 (r = 0.343, p = 0.004) and MMP-9 (r = 0.509, p = 0.042).ConclusionThe activation of the GSDMD-NETs axis is strongly associated with the development of SIC, glycocalyx injury, and adverse clinical outcomes in sepsis, potentially contributing to these pathological processes. Plasma N-GSDMD and MPO-DNA serve as predictive biomarkers for SIC severity and mortality, highlighting their potential role in targeted therapeutic strategies.